Uganda : Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
The Joint Staff Assessment reviews the government's progress in implementing the Uganda Poverty Eradication Action Plan (PEAP), and serves as Uganda's third annual Poverty Reduction Strategy Paper (PRSP) progress report. The Report indicates that the government has made satisfactory progress in implementing the PEAP. The staff of the Bank and IMF assessed that Uganda's efforts toward implementation of the poverty reduction strategy provide adequate evidence of its continued commitment to poverty reduction, and therefore the strategy remains a sound basis for Bank and IMF concessional assistance.